2019
DOI: 10.1039/c9cy01259a
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of furfural to biofuel precursors via aldol condensation with acetone over magnesium hydroxide fluorides MgF2−x(OH)x

Abstract: MgF2−x(OH)x catalysts involving neighboring Lewis acid sites and moderate strength basic sites were used successfully in aldol condensation of furfural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Based on these results and supportive literature data, 20,[44][45][46]72 the overall mechanistic proposal for Fur conversion is presented in Scheme 2. According to the literature, C8 may be formed via dehydration of the intermediate 4-(furan-2-yl)-4-hydroxybutan-2-one (C8OH), 22,43,[72][73][74] and, on the other hand, C13 may be formed via the dehydration of the intermediate 1,5-di(furan-2yl)-5-hydroxypent-1-en-3-one (C13OH). 16,22,23,43 C8OH is relatively unstable (may rapidly dehydrate to the α,β-unsaturated ketone C8), 73 which may partly explain the fact that C8OH was always present in very small amounts (<3% yield).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Based on these results and supportive literature data, 20,[44][45][46]72 the overall mechanistic proposal for Fur conversion is presented in Scheme 2. According to the literature, C8 may be formed via dehydration of the intermediate 4-(furan-2-yl)-4-hydroxybutan-2-one (C8OH), 22,43,[72][73][74] and, on the other hand, C13 may be formed via the dehydration of the intermediate 1,5-di(furan-2yl)-5-hydroxypent-1-en-3-one (C13OH). 16,22,23,43 C8OH is relatively unstable (may rapidly dehydrate to the α,β-unsaturated ketone C8), 73 which may partly explain the fact that C8OH was always present in very small amounts (<3% yield).…”
Section: Resultssupporting
confidence: 62%
“…The fact that the total selectivity was lower than 100% for the two tests suggested that C8 and/or the remaining products may be partly converted to byproducts. Based on these results and supportive literature data, 20,[44][45][46]72 the overall mechanistic proposal for Fur conversion is presented in Scheme 2. According to the literature, C8 may be formed via dehydration of the intermediate 4-(furan-2-yl)-4-hydroxybutan-2-one (C8OH), 22,43,[72][73][74] and, on the other hand, C13 may be formed via the dehydration of the intermediate 1,5-di(furan-2yl)-5-hydroxypent-1-en-3-one (C13OH).…”
Section: Resultssupporting
confidence: 62%
“…), etc. 24,25 These catalysts are conducive to the effective conversion of BDPC for the production of high-quality biofuels. However, the solidphase heavy components are primarily formed in A-K condensation process, resulting in the deactivation of most catalysts due to the deposition of the components on the surface of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pure MgF 2 is considered to be a suitable and effective sintering additive for the preparation of certain types of ceramics, 28,29 in manufacturing transparent IR windows, 30 in solar thermal technology, 31 MgF 2−x (OH) x during aldol condensation of furfural and acetone. 32 On the occasion of the 27th UN Climate Change Conference of the Parties (COP27), which will be held in Sharm el-Sheikh, Egypt, in November 2022, two research teams from South Valley University (Egypt) and Queen's University Belfast (UK) collaborated in a vital effort to combat global warming. Herein, our samples were prepared using a direct and simple method and exhibited a relatively high surface area and a superior reactivity toward CO 2 capture at 5 and 30 °C, despite a limited CO 2 flow time (1 h) throughout the samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, this study can be viewed as proactive research into using these mixtures. Furthermore, pure MgF 2 is considered to be a suitable and effective sintering additive for the preparation of certain types of ceramics, , in manufacturing transparent IR windows, in solar thermal technology, and as a catalyst in the form of MgF 2– x (OH) x during aldol condensation of furfural and acetone …”
Section: Introductionmentioning
confidence: 99%